Pengaruh Status Quo, Herding Behaviour, Representativeness Bias, Mental Accounting, serta Regret Aversion Bias terhadap Keputusan Investasi Investor Milenial di Kota Surabaya - Mahadevi, Syifa Aulia; Haryono, Nadia Asandimitra (UNESA In Collaboration With APSMBI (Aliansi Program Studi dan Bisnis Indonesia), 2021)
Investment activity in Indonesia steadily increases as more people become aware of the investment's value and potential returns. This study aims to determine the impact of status quo bias, herding behavior, representation, and mental accounting on the investment decisions of millennial investors in Surabaya. This study is conclusive because it used purposive and snowball sampling techniques to obtain samples by distributing online questionnaires—the research sample as many as 241 respondents. The analysis technique uses Structural Equation Model (SEM). This study focuses on millennial investors registered with the Indonesian Central Securities Depository (KSEI) and securities firms in Surabaya. The findings suggest that the variables status quo and regret aversion significantly bias investment decisions, whereas herding behavior, representativeness, and mental accounting do not affect investment decisions. Thus, this study can assist various parties, particularly millennial investors, pay more attention to their biases and be more cautious when making investment decisions